2015
DOI: 10.1097/ncc.0000000000000212
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Psychoeducational Interventions Focused on Sexuality in Cancer

Abstract: These results provide empirical data for evidence-based practice and inform the development of useful intervention programs through a comprehensive review and meta-analysis of the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Considering the reasons why the participants did not start and did not complete the intervention, even if they are only five sessions, the following modifications are proposed: the combination of face‐to‐face sessions and over the telephone, with the purpose of obtaining the adherence of the participants who have complications or side effects for their disease. This is suggested because a study determined that face‐to‐face psychoeducational intervention combined with telephone or the internet shows a higher effect size than both intervention independently …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the reasons why the participants did not start and did not complete the intervention, even if they are only five sessions, the following modifications are proposed: the combination of face‐to‐face sessions and over the telephone, with the purpose of obtaining the adherence of the participants who have complications or side effects for their disease. This is suggested because a study determined that face‐to‐face psychoeducational intervention combined with telephone or the internet shows a higher effect size than both intervention independently …”
Section: Discussionmentioning
confidence: 99%
“…This is suggested because a study determined that face-to-face psychoeducational intervention combined with telephone or the internet shows a higher effect size than both intervention independently. 35 The The importance of these results in posttraumatic stress lies on the fact that this variable increases the likelihood of 15-fold increase for the depression clinical level in outpatients with gastric cancer. 36 Additionally, Pereira et al 3 mention that those in chemotherapy are at higher risk of developing traumatic stress symptoms because the patients with radiotherapy and chemotherapy have less control on the treatments and perceive that their cancer is more severe; for this reason, they consider that there should be interest to continue offering psychotherapy interventions after surgery and in adjuvant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Research on couple-based interventions for sexual concerns has adopted a wide-ranging approach encompassing relational, psychological and educational support and has used different ways of delivering the interventions, for example, face-to-face, written information, telephone calls and web-based learning (Brotto et al, 2010;Kim, Yang, & Hwang, 2015;Scott & Kayser, 2009). Previous reviews have mainly included couples with prostate and breast cancer, and no systematic review has specifically addressed the study characteristics of couple-based interventions regarding sexuality concerns that include all cancer types (Chambers, Pinnock, Lepore, Hughes, & O'Connell, 2011;Scott & Kayser, 2009;Taylor, Harley, Ziegler, Brown, & Velikova, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…(18) Marcus et al (15) inferred that the printed material, although widely used by participants, did not have a great effect when compared to telephone consultations. (29,30) The literature has pointed that interventions based on couples were more efficient to improve their communication, to reduce psychological suffering and to enhance the relationship functioning. (31) Interventions based on couples were effective to promote communication, sexual adjustment and functional relationships with a better understanding of the cancer diagnosis within couples, whereas interventions based on individuals were more effective to improve the results than in group approaches and in the group combined with individual intervention.…”
Section: Discussionmentioning
confidence: 99%
“…(31) Interventions based on couples were effective to promote communication, sexual adjustment and functional relationships with a better understanding of the cancer diagnosis within couples, whereas interventions based on individuals were more effective to improve the results than in group approaches and in the group combined with individual intervention. (30)(31)(32) With regard to the tools used to train professionals, a long-lasting prospective response was found in the behavior of nurses who were submitted to professional enhancement, increasing the number of nurses who started a discussion about sexual health before patients had started their treatment, and professionals reported that they had gained enough knowledge, proper training and felt more confident in their ability to address the topic. (21) However, even though the improvements had been reported in the communication of sexual health problems with patients over time, the frequency of these discussions remained below to what is considered acceptable, despite great efforts, since most participants did not reach the goal of discussing sexual health issues with more than 50% of their patients.…”
Section: Discussionmentioning
confidence: 99%